Dr hedgehog - Mushin; Jerry (Leicester Sweet Cherry Publishing, 2014)
In this story, Mavis Mouse cannot find her son. Martin Mouse has fallen into a post-box and cannot climb out. How does Dr Hedgehog get him out?